Arqueobotânica no sítio Terra Preta do Mangabal, região do alto rio Tapajós - Pinheiro, Natálya Cristiana Pereira (2021)
The present work proposes to investigate the relationship between people and plants in the upper Tapajós river from 1,200 years before the present (BP). The research study is based on the archaeobotanical remains recovered from the Terra Preta do Mangabal archaeological site, in the municipality of Itaituba, southwestern Pará. This site is found within the territory traditionally occupied by riverine people, descedants of rubber tappers and indigenous women, located within a Project of Agroextractive Settlement Montanha and Mangabal. To carry out this proposal, we will discuss the perspectives that have guided archaeobotanical studies, especially regardind the way in which they enable to contemplate and explore the issue of diversity. When closing the focus on the studied region, we will present an outline of the historical process of regional occupation through archaeological and ethno-historical works. Macroremains from the Terra Preta do Mangabal site, situated adjacente to strech of rapids the Tapajós river, will be an important point for reflection over the use of plants and spaces, as well as the human contributions to the floristic composition of its the region or the sites current vegetation.